Robotic-assisted vs traditional laparoscopic surgery for endometrial cancer: a randomized controlled trial - Mäenpää, Minna M.; Nieminen, Kari; Tomás, Eija I.; Laurila, Marita; Luukkaala, Tiina H.; Mäenpää, Johanna U. (American journal of obstetrics and gynecology, 2016)
Previous studies comparing robotic-assisted laparoscopic surgery to traditional laparoscopic or open surgery in gynecologic oncology have been retrospective. To our knowledge, no prospective randomized trials have thus far been performed on endometrial cancer. We sought to prospectively compare traditional and robotic-assisted laparoscopic surgery for endometrial cancer. This was a randomized controlled trial. From December 2010 through October 2013, 101 endometrial cancer patients were randomized to hysterectomy, bilateral salpingo-oophorectomy, and pelvic lymphadenectomy either by robotic-assisted laparoscopic surgery or by traditional laparoscopy. The primary outcome measure was overall operation time. The secondary outcome measures included total time spent in the operating room, and surgical outcome (number of lymph nodes harvested, complications, and recovery). The study was powered to show at least a 25% difference in the operation time using 2-sided significance level of .05. The differences between the traditional laparoscopy and the robotic surgery groups were tested by Pearson χ2 test, Fisher exact test, or Mann-Whitney test. In all, 99 patients were eligible for analysis. The median operation time in the traditional laparoscopy group (n = 49) was 170 (range 126-259) minutes and in the robotic surgery group (n = 50) was 139 (range 86-197) minutes, respectively (P < .001). The total time spent in the operating room was shorter in the robotic surgery group (228 vs 197 minutes, P < .001). In the traditional laparoscopy group, there were 5 conversions to laparotomy vs none in the robotic surgery group (P = .027). There were no differences as to the number of lymph nodes removed, bleeding, or the length of postoperative hospital stay. Four (8%) vs no (0%) patients (P = .056) had intraoperative complications and 5 (10%) vs 11 (22%) (P = .111) had major postoperative complications in the traditional and robotic surgery groups, respectively. In patients with endometrial cancer, robotic-assisted laparoscopic surgery was faster to perform than traditional laparoscopy. Also total time spent in the operation room was shorter in the robotic surgery group and all conversions to laparotomy occurred in the traditional laparoscopy group. Otherwise, the surgical outcome was similar between the groups. Robotic surgery offers an effective and safe alternative in the surgical treatment of endometrial cancer.